Supplier Selection with Fuzzy AHP for Multi Decision Makers Case Study: Animal Feed Factory PT. XYZ - Erwin Tri Gunawan; Joniarto Parung* (Riwayat: Educational Journal of History and Humanities, 2023)
Multi-criteria decision-making or Multi-Criteria Decision-Making (MCDM) is a quantitative method used to determine the ranking or the best solution from several alternative choices by considering many criteria. The Analytical Hierarchy Process (AHP) is one of the MCDM methods that is very popular and acceptable because of its simplicity but being able to answer the needs of decision makers in complex situations. However, the dynamics in the industry have finally concluded that AHP is no longer suitable for making decisions when the information is uncertain and unclear. An alternative solution is to integrate the Fuzzy sets method with AHP as an approach to dealing with multi-criteria problems in conditions of uncertain information. Decision making in Fuzzy-AHP, as in other methods, is carried out by individuals or groups who jointly make decisions on a problem. However, problems arise when in a group there are individuals who are dominant but do not understand the topic or criteria used in decision making. This can lead to decisions taken that are not in accordance with expectations or are often called biased decisions. To overcome this, decision makers in groups need to make judgments independently, and each decision maker is given a weight according to the quality of his decision. The end result of this research is the development of the Fuzzy AHP model with the participation of multiple decision makers in supplier selection at the Animal Feed Factory of PT. XYZ. This model allows decision makers to provide independent assessments and give weight according to the quality of their decisions, resulting in more accurate and integrated decisions. It is hoped that this model will make a positive contribution to management at PT. XYZ in choosing suppliers that are optimal and can support operational sustainability and the company's competitive advantage.